Magnetically recyclable CoFe2O4/ZnO nanocatalysts for the efficient catalytic degradation of Acid Blue 113 under ambient conditions. Issue 28 (25th April 2020) - Krishna, S.; Sathishkumar, P.; Pugazhenthiran, N.; Guesh, Kiros; Mangalaraja, R. V.; Kumaran, S.; Gracia-Pinilla, M. A.; Anandan, S.
Abstract : CoFe2 O4 /ZnO magnetic nanocatalysts were synthesized using a low-frequency ultrasound-assisted technique to enhance the optical, morphological, magnetic and catalytic properties of ZnO. Abstract : CoFe2 O4 /ZnO magnetic nanocatalysts were synthesized using a low-frequency ultrasound-assisted technique to enhance the optical, morphological, magnetic and catalytic properties of ZnO. The as-synthesized nanocatalysts were characterized by XRD, Raman, TEM, DR-UV-Vis and VSM analyses in order to confirm the expected modifications of the resulting nanocatalysts. The Raman spectral analysis revealed substitutional Zn 2+ in the CoFe2 O4 /ZnO nanocatalyst. The as-synthesized material was tested for its catalytic activity in the degradation of Acid Blue (AB113), a known textile pollutant. The CoFe2 O4 and CoFe2 O4 /ZnO nanocatalysts revealed the efficient catalytic degradation of AB113 in ambient conditions. The nanocatalyst dosage and the initial concentration of AB113 were varied by fixing one parameter as constant in order to determine the maximum catalytic efficiency with the minimum catalyst loading for AB113 degradation. The CoFe2 O4 /ZnO nanocatalyst demonstrated 10-fold enhanced mineralization of AB113 compared to the individual bare nanocatalysts, which could be achieved within 3 hours of catalytic degradation of AB113. The magnetic CoFe2 O4 /ZnO nanocatalyst was found to be stable for six consecutive recycles of AB113 degradation, which indicates that the catalytic efficiency of the nanocatalyst was retained after various numbers of cycles.